Jeden cel – dwie drogi: O recepcji wzorców francuskich na przykładzie krakowskiej i warszawskiej szkoły nauk politycznych od czasów zaborów do 1939 r. (Politeja, 2015)
One Goal – Two Roads: Reception of the French Model on the Example of the Cracow and Warsaw Schools of Political Sciences From the Partitions of Poland to 1939This paper aims to present how École Libre des Sciences Politiques in Paris affected the development of political sciences in Poland. Two schools based on the French model were set up in Cracow and Warsaw by Michał Rostworowski and Edmund Jan Reyman, former students of the French school. In this article, the Warsaw School of Political Sciences and the Jagiellonian University’s School of Political Sciences are described from the perspective adopted by Rostworowski in his study devoted to École Libre des Sciences Politiques. The paper describes the attempts to adapt the French model to the Polish conditions and shows two ways of its reception. The Warsaw school gained an academic status and became an all‑Polish centre of political sciences while the school in Cracow was incorporated into the Jagiellonian University and created an academic environment based on the master‑disciple relationship. It marked the beginning of what Marek Sobolewski described as the Cracow school of political sciences.